Automation or Meaning? Socialism, Humanism and Cybernetics in Etarea. Issue 1 (15th April 2019) - Krivý, Maroš
Abstract : Designed in 1967 for a site near Prague, Czechoslovakia, and exhibited that year at the Montreal Expo, Etarea was to be a city of 135, 000 inhabitants, where the conveniences of automated infrastructure would satisfy future socialist generations. Conceived by the architect Gorazd Čelechovský as the ideal communist city, the case offers compelling insight into the influence of Marxist humanism and systems theory on post-war and specifically post-Stalinist state socialist architectural culture. Informed by these intellectual currents, as the article details, Etarea placed the question of meaning at centre stage. Meaning in architecture was considered in terms of both cybernetic communication and existential phenomenology, and its function was no less than to advance the communist transition. Etarea was informed by Civilization at the Crossroads (1966 ), an influential policy treatise that emphasized the significance of the intelligentsia and the so-called 'scientific and technological revolution' to future communism. The article explores the function of the 'living environment' as a conceptual banner and link between the publication and the project. While Civilization argued that urbanization must be decoupled from industrialization, Etarea was to be a model 'post-industrial' environment. Three aspects to Etarea are analysed in detail: the territorial question of the city-country divide, the balance between automation and socio-psychological meaning and tensions between political emancipation and cybernetic control.